Current developments in renewable energy resources-based hybrid energy system: a review. (2016) - Siddiqui, A.J.; Bharadwaj, S.K.; Kothari, D.P.; Deshmukh, Bhupendra
The key drivers for increasing the use of renewable energy are large and un-explored potential, a gap between demand and supply to increase in potency, and environment concerns. The maximum available potential at all sites are majorly wind and solar energy, but due to the high unpredictable nature of wind, designing a system based on only wind energy may not be technically viable, therefore, a combination of renewable energy sources is fascinating researchers to design and implement the power system in a developing country leads the development of the hybrid energy system. Research and development in the field of solar, wind other renewable energy sources will be the future substitute in meeting the demand and supply gap of power. This paper presents a review of work done by various researchers in the area of pre-feasibility, unit sizing, modelling, and operation and control of various hybrid renewable energy systems.